A Hypomorphic PALB2 Allele Gives Rise to an Unusual Form of FA-N Associated with Lymphoid Tumour Development. - Philip J Byrd; Grant S Stewart; Anna Smith; Charlotte Eaton; Alexander J Taylor; Chloe Guy; Ieva Eringyte; Peggy Fooks; James I Last; Robert Horsley; Antony W Oliver; Dragana Janic; et al. (PLoS Genetics)
Patients with biallelic truncating mutations in PALB2 have a severe form of Fanconi anaemia (FA-N), with a predisposition for developing embryonal-type tumours in infancy. Here we describe two unusual patients from a single family, carrying biallelic PALB2 mutations, one truncating, c.1676_1677delAAinsG;(p.Gln559ArgfsTer2), and the second, c.2586+1G>A; p.Thr839_Lys862del resulting in an in frame skip of exon 6 (24 amino acids). Strikingly, the affected individuals did not exhibit the severe developmental defects typical of FA-N patients and initially presented with B cell non-Hodgkin lymphoma. The expressed p.Thr839_Lys862del mutant PALB2 protein retained the ability to interact with BRCA2, previously unreported in FA-N patients. There was also a large increased chromosomal radiosensitivity following irradiation in G2 and increased sensitivity to mitomycin C. Although patient cells were unable to form Rad51 foci following exposure to either DNA damaging agent, U2OS cells, in which the mutant PALB2 with in frame skip of exon 6 was induced, did show recruitment of Rad51 to foci following damage. We conclude that a very mild form of FA-N exists arising from a hypomorphic PALB2 allele.